Análise eletroencefalográfica e comportamental da convulsão provocada por lidocaína, um anestésico local - SOUZA, Alisson Santos de (2020)
Local anesthetics were discovered in 1860, by the extraction of cocaine from Erythroxylon coca leaves. Lidocaine was synthesized by Löfgren in 1943, giving rise to the use of amidetype local anesthetics. They act on cell membranes and reversibly block nerve conduction. If a large amount of local anesthetic reaches the bloodstream, dose-related complications will be noticeable both in the central nervous system and in the heart. Agitation may be the first sign of intoxication, since anesthetics act first upon inhibitory neurons, possibly leading to seizure depending on plasma concentration. The behavioral, encephalographic and electromyographic parameters of seizure induced by toxic doses of lidocaine and the response to anticonvulsants were analyzed in this research. An experimental study was conducted in 27 adult Wistar rats weighing 200 to 290g treated with 20mg/kg lidocaine intraperitoneally. After lidocaine administration, behavioral changes and the evolution of convulsive crisis were observed for 60 minutes. Changes in the electroencephalographic records presented activity with variations of amplitude that characterized the convulsive event and performance of the drugs upon crisis control. With regard to the anticonvulsant drugs, diazepam was the most effective drug in controlling seizures. Phenobarbital did not adequately control convulsions, but decreased repetition frequency of the phenomenon. Phenytoin had the least effect on peak control in the electroencephalographic record of seizures caused by toxic doses of lidocaine.